Vital bone formation after grafting of autogenous bone and biphasic calcium phosphate bioceramic in extraction sockets of rats: Histological, histometric, and immunohistochemical evaluation - Macedo, Rander Moreira; Lacerda, Suzie Aparecida; Okamoto, Roberta [UNESP]; Shahdad, Shakeel; Brentegani, Luiz Guilherme (Wolters Kluwer, 2018)
Purpose: The study aimed to investigate through histology, histometry, and immunohistochemistry the vital bone formation after grafting of biphasic calcium phosphate bioceramic (BC) in combination with calvarial autogenous bone into the dental sockets of rats. Materials and Methods: Fortyfive male rats were submitted to upper right incisor extraction and divided according to the grafted material in: control, bioceramic (BC), and bioceramic + autogenous bone (BC + AB). The animals were killed 7, 21, and 42 days after surgery for histological, histometric, and immunohistochemistry analysis. Results: Histomorphometric results demonstrated, for BC + AB group, formation of trabecular bone between the particles of BCs and autogenous bone, connecting them, as well as higher percentage of vital bone in comparison with BC. Immunohistochemical reactions showed intense labeling for Runx2-positive cells in the group BC + AB. Conclusions: Autogenous bone was able to stimulate bone turnover enabling a larger amount of vital bone synthesis and can be recommended as a viable grafting material in combination with synthetic biphasic BC.
Keywords: Animal study; Bone graft; Bone substitutes; Extraction socket